2017
DOI: 10.1002/aoc.3740
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biological activities of two novel orthopalladated complexes: Interactions with DNA and bovine serum albumin, antitumour activity and molecular docking studies

Abstract: [Pd(L 1 )(C,N)]CF 3 SO 3 and [Pd(L 2 )(C,N)]CF 3 SO 3 (L 1 = 2,2′-bipyridine, L 2 = 1,10-phenanthroline and C,N = benzylamine) novel orthopalladated complexes have been synthesized and characterized using various techniques. The binding of the complexes with native calf thymus DNA (CT-DNA) was monitored using UVvisible absorption spectrophotometry, fluorescence spectroscopy and thermal denaturation studies. Our results indicate that these complexes can strongly bind to CT-DNA via partial intercalative mode. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 68 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…In complex A and complex B docking with DNA, the lowest free binding energy values are almost the same, but molecular docking with BSA results in the buthylbenzylamine complexes; complex C has noticeably more value in comparison to complex D , this is agreement with the experimental value of binding energy. The obtained conformers from molecular docking of complexes to DNA have shown the groove‐binding mode interaction as well as the spectroscopy experiment (Figure ), indicating the lowest free binding energy conformer in docking between four complexes and DNA that is similar to palladium complexes contain similar amines . The conformers of docking were analyzed to determine the interaction of DNA and complexes as well as examining the hydrogen bond and π–π stacking interaction among them.…”
Section: Resultsmentioning
confidence: 99%
“…In complex A and complex B docking with DNA, the lowest free binding energy values are almost the same, but molecular docking with BSA results in the buthylbenzylamine complexes; complex C has noticeably more value in comparison to complex D , this is agreement with the experimental value of binding energy. The obtained conformers from molecular docking of complexes to DNA have shown the groove‐binding mode interaction as well as the spectroscopy experiment (Figure ), indicating the lowest free binding energy conformer in docking between four complexes and DNA that is similar to palladium complexes contain similar amines . The conformers of docking were analyzed to determine the interaction of DNA and complexes as well as examining the hydrogen bond and π–π stacking interaction among them.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicated that the interaction between water molecules and complex III did not include formation of covalent bands, therefore complex formation between water and Pd was almost impossible. Third, the chemical structure of the cyclopalladated complexes was mostly stable, reducing the chance of the water molecule to act as a ligating agent . Fourth, as can be seen from Figures and , addition of water to the organic solution of complex III did not induce a marked shift in the wavelength range of the absorption and fluorescence spectra of complex III .…”
Section: Resultsmentioning
confidence: 90%
“…The organometallic motifs by us so far examined included Pd(II)-allyls, [21][22][23][24][25][26][27] palladacyclopentadienyls, [27,28,29] Pd(0)-olefins [27,30] and more recently Pd(II)-indenyls, [31][32][33] while other research groups turned their attention to Pd(II)-alkynyls [34] and an extensive panel of cyclopalladates. [19,[35][36][37][38] All these works indicate the primary importance of the organic fragment in determining the activity of the complex although it can be modulated by a careful choice of the ancillary ligands. It is therefore a good strategy to endeavour of expanding the library of palladium complexes tested as anti-proliferative agents towards cancer cells, although not being easily able to predict their effectiveness in advance.…”
Section: Introductionmentioning
confidence: 99%
“…Also our group has been involved in this topic, preparing and testing as anticancer agents, a large number of organopalladium complexes. The organometallic motifs by us so far examined included Pd(II)‐allyls, [21–27] palladacyclopentadienyls, [27,28,29] Pd(0)‐olefins [27,30] and more recently Pd(II)‐indenyls, [31–33] while other research groups turned their attention to Pd(II)‐alkynyls [34] and an extensive panel of cyclopalladates [19,35–38] . All these works indicate the primary importance of the organic fragment in determining the activity of the complex although it can be modulated by a careful choice of the ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%